Examination of Muslim asset-distribution practices in Malaysia and its Link to land fragmentation problems - Khalid, Haniza (2011)
The practice of distributing a deceased’s assets based on the literal application of the Faraid calculations is often linked to the dire problem of land fragmentation and low rural land values prevalent in Malaysia today. The overall result is uneconomic land sizes and farm operations, conversion of agricultural land to other uses (and hence, the subsequent decline of food production capabilities of the country as a whole) and erosion of total Malay-Muslim land ownership and economic wealth. All of these outcomes go against the concept of Maqasid-al-Shariah particularly with respect to preserving the Maal and income of the Muslims.This paper seeks to evaluate the land fragmentation issue as linked to the asset distribution practice amongst Malay-Muslims in Malaysia. Hopefully, it can trigger more in-depth research to better inform policy-improvement measures by the present land and Muslim affair authorities.